2006
DOI: 10.1111/j.2151-6952.2006.tb00229.x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Teachers' Perspectives on Field Trips: Discovering Common Ground in Three Countries

Abstract: The school field trip constitutes an important demographic market for museums. Field trips enlist the energies of teachers and students, schools and museums, and ought to be used to the best of their potential. There is evidence from the literature and from practitioners that museums often struggle to understand the needs of teachers, who make the key decisions in field trip planning and implementation. Museum personnel ponder how to design their programs to serve educational and pedagogical needs most effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0
15

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(99 citation statements)
references
References 39 publications
(3 reference statements)
3
77
0
15
Order By: Relevance
“…advance content preparation, active participation in structured science activities, and follow-up activities (National Research Council, 2009). Recent research has shown that advance field trip preparation gives students a framework which guides what they should pay attention to during the visit and how they should interpret what they see (D. Anderson, Kisiel, & Storksdieck, 2006;D. Anderson, Lucas, Ginns, & Dierking, 2000;Griffin & Symington, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…advance content preparation, active participation in structured science activities, and follow-up activities (National Research Council, 2009). Recent research has shown that advance field trip preparation gives students a framework which guides what they should pay attention to during the visit and how they should interpret what they see (D. Anderson, Kisiel, & Storksdieck, 2006;D. Anderson, Lucas, Ginns, & Dierking, 2000;Griffin & Symington, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, an effective linkage of in-and out-of-school learning is difficult to achieve. Anderson, Kisiel and Storksdieck advise people offering field trip opportunities to consider directing their attention towards the teachers' needs, particularly because teachers seem to have multiple objectives [53]. The authors emphasize that both affective and cognitive objectives are the goal of the teachers.…”
Section: Effective Structuring Of Non-formal Learningmentioning
confidence: 99%
“…La literatura internacional da cuenta de un grupo importante de trabajos, tanto en el plano de la indagación de las opiniones y percepciones de los docentes con respecto a los museos, el patrimonio, las colecciones, y su posibilidad y potencialidad como recurso para la enseñanza (por ejemplo Anderson, Kisel y Storksdieck, 2006); así como en el plano del diseño, ejecución y valoración de cursos o espacios para la capacitación y la formación de los profesores en el contexto de la relación museo-escuela (por ejemplo Leinhardt y Gregg, 2002).…”
Section: Las Encuestas Siguen Informando Que La Mayoría De Los Profesunclassified
“…Entre los factores identificados se destacan la relación con los contenidos curriculares, la relevancia histórica y cultural del sitio, el acceso y logística, así como las visitas y las experiencias previas de los docentes. Anderson, Kisel y Storksdieck (2006) abordan las problemáticas comunes que enfrentan profesores de tres países diferentes (Estados Unidos, Canadá y Alemania), a la hora de realizar una visita con sus estudiantes, así como las sugerencias y propuestas para mejorar la relación entre los museos y las escuelas. Dentro de los problemas detectados, sobresalen las dificultades propias de relacionar dos sistemas educativos con filosofías y propósitos distintos (formal e informal) y entre los más acuciantes, se señalan: la comunicación y cooperación, la dicotomía entre la logístico y lo pedagógico, el acceso y uso de los materiales y la formación de los docentes en el uso de recursos no convencionales.…”
Section: Las Encuestas Siguen Informando Que La Mayoría De Los Profesunclassified